O papel da bioenergética mitocondrial e estresse oxidativo no comportamento depressivo em modelo de concussão recorrente em camundongos - Feiteiro, Leandro Machado Severo (2020)
The traumatic brain injury (TBI) is one lesion occasioned by the mechanical application of a force external to the brain. Currently, 80 to 90% of cases of TBIs are considered concussion or mild TBI, in which contain the symptoms commonly resolved in the first weeks following injury. On the other hand, recurrent episodes of mild TBI or concussion lifelong can alter neurochemistry of encephalon in which are linked with brain atrophy, production of reactive oxygen species and reactive nitrogen species (ROS/RNS), mitochondrial dysfunction, and inflammation. These changes can trigger emergence of diseases, such as major depression, disorder psychiatric with great incidence after TBI. Despite this, Most of the research of this injury has been focused on oxidative stress and functional deficits; however, mechanisms that underlie the development of neuropsychiatric disorders remain little researched. Due to this, the present authors investigated the involvement of the mitochondrial metabolism and of the oxidative stress in a possible depressive behavior induced for a recurrent concussion protocol in mice. In this way, the rodents were submitted to different numbers of injuries (4, 7 and 10 traumas), and the immobility time was evaluated by the tail suspension test (TSC), as well as, mitochondrial bioenergetics was analyzed by high-resolution respirometry (OROBOROS, Instruments). In addition, the levels of reactive oxygen species (ROS), as well as, the rate of antioxidant defenses were measured at the hippocampus of mice. The experimental data revealed, for the first time, that the present protocol of recurrent concussions (4, 7, and 10 injuries) in mice did not alter immobility time during tail suspension tests (TSTs), but decreased hippocampal mitochondrial respiration and increased expression of proteins such as nuclear factor erythroid 2-related factor 2 (Nrf2) and superoxide (SOD2). This experimental data suggests that bioenergetic changes elicited by recurrent concussion did not induce depressivelike behavior, but activated the transcription factor of responsive antioxidant elements (ARE) that delay or prevent secondary cascades in this neurological disease.